Metabolic Syndrome and Cardiovascular Risk Factors in Obese Adolescent - Mansour, Manal (Open Access Maced J Med Sci, 2016)
BACKGROUND: Childhood and adolescent obesity is associated with insulin resistance, abnormal glucose metabolism, hypertension, dyslipidemia, inflammation, liver disease, and compromised vascular function. The purpose of this study was to determine the prevalence of cardiovascular risk factor abnormalities and metabolic syndrome in a sample of obese adolescent as prevalence data might be helpful in improving engagement with obesity treatment in future. The high blood lipid levels and obesity are the main risk factors for cardio vascular diseases. Atherosclerotic process begins in childhood. AIM: This study aimed to investigate the relationship between obesity in adolescent and their blood lipids levels and blood glucose level. METHODS: This study was conducted with 100 adolescents of both gender age 12-17 years and body mass index (BMI) greater than 95th percentiles and 100 normal adolescents as control group. The blood samples were collected from all adolescents after overnight fasting (10 hours) to analyze blood lipids (Total cholesterol, high density lipoprotein, low density lipoprotein) and hematological profile (Hemoglobin, platelets and red blood cell, C reactive protein and fasting blood glucose. RESULTS: There were statistical difference between the two groups for red blood cells (P<0.001), Hemoglobin (P < 0.001) and platelets (P = 0.002), CRP (P = 0.02). Positive correlation was found between the two groups as regards total cholesterol (P = 0.0001), P value was positive for HDL (P = 0.005 and Atherogenic index P value was positive (P = 0.002). Positive correlation was found between the two group as regards fasting blood glucose (P = 0.001). CONCLUSION: Saturated fat was associated with elevated lipid levels in obese children. These results reinforce the importance of healthy dietary habits since child-hood in order to reduce the risks of cardiovascular diseases in adulthood.